Tumor-infiltrating lymphocytes in triple negative breast cancer - L. M. Zakhartseva; M. O. Yanovytska (Patologìâ)
The aim of this retrospective study is to assess the prognostic value of tumor-infiltrating lymphocytes in triple negative breast carcinomas that lack both estrogen, progesterone receptors and Her2 amplification.